1999
DOI: 10.1074/jbc.274.53.37551
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial Na+/H+ Exchanger, NHE3, Is Internalized through a Clathrin-mediated Pathway

Abstract: Trafficking of the Na ؉ /H؉ exchanger isoform 3 (NHE3) between sub-apical vesicles and apical membrane of epithelial cells is a suggested mechanism of regulation of NHE3 activity. When epitope-tagged NHE3 was stably expressed in NHE-deficient Chinese hamster ovary cells, a sizable fraction was found in recycling endosomes. This system was used to analyze the mechanism of endocytosis of NHE3. Immunofluorescence and radiolabeling experiments showed that inhibition of clathrinmediated endocytosis using hypertonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 69 publications
(74 reference statements)
6
92
0
1
Order By: Relevance
“…It was recently shown that endocytosis of NHE3 occurs primarily via clathrin-coated pits (36,37) and that clathrin-mediated endocytosis requires an intact actin cytoskeleton (38). In support of trafficking, we demonstrated that the decrease of NHE3 activity induced by CPA is inhibited by cytochalasin B, which induces cytoskeletal disorganization (31) and reportedly has per se an inhibitory effect on NHE3 (31) (for effect of cytochalasin B, see also the Results section).…”
Section: Discussionsupporting
confidence: 78%
“…It was recently shown that endocytosis of NHE3 occurs primarily via clathrin-coated pits (36,37) and that clathrin-mediated endocytosis requires an intact actin cytoskeleton (38). In support of trafficking, we demonstrated that the decrease of NHE3 activity induced by CPA is inhibited by cytochalasin B, which induces cytoskeletal disorganization (31) and reportedly has per se an inhibitory effect on NHE3 (31) (for effect of cytochalasin B, see also the Results section).…”
Section: Discussionsupporting
confidence: 78%
“…CHP1 is involved in targeting/fusion of transcytotic vesicles with the apical membrane (25). Although, NHE3 is endocytosed into clathrin-coated vesicles (40,71), exactly how CHP regulates NHE3 trafficking is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis has been implicated previously (17,18) in regulation of NHE3 activity by alteration of the amount of NHE3 localized in the plasma membrane. The intracellular localization of NHE3 in the recycling compartment was demonstrated both in nonepithelial cells, PS120 and AP-1 fibroblasts, and in epithelial cells, including Caco-2 and OK epithelial cells (17,18,30,40).…”
Section: Inhibition Of Namentioning
confidence: 99%
“…Another mechanism for acute regulation of NHE3 activity includes membrane trafficking between an intracellular recycling compartment and the plasma membrane (17)(18)(19). NHE3 is active on the plasma membrane, and the alteration of surface NHE3 protein abundance plays a role in regulation of NHE3 activity by extracellular agonists including peptide hormones, growth factors, and neurotransmitters (1).…”
mentioning
confidence: 99%